The psychometric properties of the Jordanian version of the Modified Checklist for Autism in Toddlers-Revised (M-Chat-R/F) - Rola Altiti; Ali M. Alodat (Springer, 2024)
Abstract This study aims to explore the psychometric properties of the Jordanian version of the Modified Checklist for Autism in Toddlers-Revised (M-Chat-R/F). The Jordanian version of M-CHAT-R/F was administered within the Jordanian context among 134 children aged between 6 and 30 months; 37 were diagnosed with autism spectrum disorder (ASD), and 97 were without ASD. The M-CHAT-R/F consists of the modified Autism Spectrum Screening Questionnaire (ASSQ) and a follow-up model. The results revealed that M-Chat-R/F demonstrates acceptable levels of validity and reliability. The content validity was deemed suitable for the Jordanian environment, and the construct validity showed that items relying on a single factor reached saturation. The results also revealed acceptable levels of reliability, with Pearson correlation coefficients ranging between 0.209 and 0.693, all positive, high, and statistically significant. The Cronbach's alpha coefficient was 0.870, the sensitivity coefficient was 0.786, and the specificity coefficient was 0.957, indicating the checklist's ability to classify cases of ASD in children. In conclusion, the M-CHAT-R/F is a highly valid and reliable instrument that can effectively classify cases of ASD in children aged between 16 and 30 months. A score of 6 or below on the checklist indicates a high probability of ASD, reaffirming the confidence in the potential of the M-CHAT-R/F checklist for healthcare professionals in the field of child development and autism spectrum disorders. Finally, this study emphasizes that the Jordanian version of M-Chat-R/F is a screening rather than a standardized diagnostic tool for ASD, underscoring the need for further validation.